Comments and Reflections on Ethics in Screening for Biomarkers of Prenatal Alcohol Exposure. (2nd April 2013) - Zizzo, Natalie; Di Pietro, Nina; Green, Courtney; Reynolds, James; Bell, Emily; Racine, Eric
Abstract : Early identification of and intervention for fetal alcohol spectrum disorder (FASD) has been shown to optimize outcomes for affected individuals. Detecting biomarkers of prenatal alcohol exposure (PAE) in neonates may assist in the identification of children at risk of FASD enabling targeted early interventions. Despite these potential benefits, complicated ethical issues arise in screening for biomarkers of PAE and these must be addressed prior to the implementation of screening programs. Here, we identify and comment, based on a North American perspective, on concerns raised in the current ethical, social, and legal literature related to meconium screening for PAE. Major ethical concerns revolve around the targeting of populations for PAE screening, consent and respect for persons, stigma and participation rates, the cost—benefit analysis of a screening program, consequences of false‐positive and false‐negative test results, confidentiality and appropriate follow‐up to positive screen results, and the use of screen results for criminal prosecution. We identify gaps in the literature on screening for PAE, most notably related to a lack of stakeholder perspectives (e.g., parents, healthcare providers) about screening and the ethical challenges it presents.